قضایا أسلوبیة بین الموروث العربي والمناھج الغربیة الحدیثة (Journal of the College of Education for Women, 2019)
Find addresses some issues of contemporary stylistic contemporaryArab scholars, and tries to answer. Issue: stylistic roots in the rhetoricalArab heritage. And the issue of reverse between old and contemporary.And proposes a new stylistic take into account the specificity of the Islamicand Arabic text is consistent with the application and analysis.